ANALISIS HAMBATAN DAN TANTANGAN IMPLEMENTASI K3 DARI PERSPEKTIF KARYAWAN PADA PT X - Utsukhusi, Marlyn Putri; Sabila, Farah Dina; Atho'illah, Akhmad Yunan (Growth, 2025)
This study aims to analyze the barriers and challenges in the implementation of Occupational Health and Safety (OHS) from the employees’ perspective at PT X. As a manufacturing company, PT X is exposed to a high level of occupational accident risks due to the use of machinery and chemical substances in its production process. Although OHS policies have been established, their effectiveness is still influenced by employees’ experiences and perceptions in the workplace. A fatal workplace accident in 2024, which resulted in one employee’s death and another suffering serious injuries, highlights the urgent need for a comprehensive evaluation of OHS implementation. This research employed a qualitative method with a case study approach, utilizing in-depth interviews and document analysis from the company as well as media reports. The findings indicate that the main barriers to OHS implementation include low employee compliance with safety procedures, limited safety facilities, and weak management supervision. The challenges identified involve a work culture that prioritizes productivity over safety, limited budget allocation, and the lack of continuous OHS training. The study concludes that improving the effectiveness of OHS requires active involvement of both management and employees in building a strong safety culture, strengthening supervision, and enhancing the quality of training and safety facilities